2020
DOI: 10.1038/s41598-020-64851-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock in Japanese forests has been greatly underestimated

Abstract: An accurate estimate of total forest carbon (c) stock and c uptake is crucial for predicting global warming scenarios and planning co 2 emission reductions. Forest inventory, based on field measurements of individual tree sizes, is considered the most accurate estimation method for forest c stock. Japan's national forest inventory (nfi) provides stand-scale stem volume for the entire forested area based on (1) direct field measurements (m-NFI) and (2) prediction using yield tables (p-NFI). Here, we show that J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
0
20
1
Order By: Relevance
“…3 We adopted the same method used in Egusa et al (2020) to calculate the amount of carbon stock per hectare.…”
Section: Converting Abandoned Agricultural Lands Into Forestsmentioning
confidence: 99%
“…3 We adopted the same method used in Egusa et al (2020) to calculate the amount of carbon stock per hectare.…”
Section: Converting Abandoned Agricultural Lands Into Forestsmentioning
confidence: 99%
“…However, approximately 90 % of the carbon stock in building wood is derived from wooden buildings, which are still a primary representative of carbon storage. The latest carbon stock in all buildings as of 2020 was 241 Tg-C, which is equal to 8 %-9 % of the amount of carbon stock [43] in Japan's forest biomass -a size that cannot be ignored when examining current and future carbon balance in forest sinks.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese law requires that the forest register be updated every 5 years. The satellite-derived AGB was more significant than the value in the register in Ibaraki, and some previous studies also concluded that the forest register underestimated the forest volume [81]. Japan's Forestry and Forest Products Research Institute compared the register's data with a field measurement at 10,189 sub-compartments throughout Japan, and found that the fieldmeasured forest volume was 1.88 times the value in the forest register for Japan as a whole [82].…”
Section: Benchmark Agb Estimated In the Japanese Forest Inventorymentioning
confidence: 99%